1988
DOI: 10.1007/bf00058736
|View full text |Cite
|
Sign up to set email alerts
|

Use of an established human hepatoma cell line with endogenous bioactivation for gene mutation studies

Abstract: Genetic toxicology assays that rely on S9 microsomal mixes are subject to artifacts related to the generation of mutagenic metabolites by acidic pHs, variation in individual isolations of microsomes and the failure of subcellular fractions to faithfully produce metabolites generated in intact cells. We have developed a gene mutation assay utilizing the human hepatoma cell line HepG2, which has been shown to metabolize a broad spectrum of promutagens. Optimal conditions for assaying the induction of 6-thioguani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Dearfield et al (17) demonstrated that the HepG2 was capable of activating cyclophosphamide to induce sister chromatid exchanges (SCEs), and demonstrated that the content of cytochrome P450 is very low in the HepG2 cells (a phenomenon that has been reported by several laboratories). Other compounds that have been reported to be activated by the HepG2 include benzo-[a] pyrene (18,19), 7,1 2-dimethylbenz- [a]anthracene (20,21), aflatoxin B1, (22,23), several N-nitroso compounds (24), benzidine (23,25), acetylbenzidine (23) (21).…”
Section: Introductionmentioning
confidence: 99%
“…Dearfield et al (17) demonstrated that the HepG2 was capable of activating cyclophosphamide to induce sister chromatid exchanges (SCEs), and demonstrated that the content of cytochrome P450 is very low in the HepG2 cells (a phenomenon that has been reported by several laboratories). Other compounds that have been reported to be activated by the HepG2 include benzo-[a] pyrene (18,19), 7,1 2-dimethylbenz- [a]anthracene (20,21), aflatoxin B1, (22,23), several N-nitroso compounds (24), benzidine (23,25), acetylbenzidine (23) (21).…”
Section: Introductionmentioning
confidence: 99%
“…HepG2, the human hepatoma cells used in this study, retain many of the functions of a normal liver cell, such as secretion of plasma lipoproteins and the synthesis of albumin and glycogen. 23,24 Also, HepG2 cells express an inducible cytochrome P-450 system, which makes them an ideal model to investigate the metabolism of genotoxins. A synthetic antioxidant, BHT, was reported to affect a number of phase II enzymes including glutathione transferase, and therefore to inhibit the binding of genotoxins to cellular macromolecules.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, considerable effort has been made to characterize, identify and quantitate these compounds in human foods and to elucidate their potential health risks [3,4] .Heterocyclic aromatic amines have been tested extensively in microbial in vitro assays such as Ames Salmonella typhimurium test [5] and are potent mutagens in these test procedures [6] however, literature survey has indicated that almost none of the studies have simultaneously employed two in vitro genocytotoxicity assays, the MTT assay and the comet assay (single cell gel electrophoresis assay) to authenticate the genotoxicity of food. further, it is well documented that HepG2 cell lines retain the activity of certain phase I enzymes involved in metabolism of genotoxic carcinogens such as cytochrome P450 cYP1A1, cYP1A2, cYP2B, cYP2E1 as well as phase II enzymes including glutathione-S-transferases, sulfotransferases, n-acteyltransferases and glucoranosyltransferases, which reflect the metabolism of heterocyclic aromatic amines [7] in mammals better than other in vitro models which require addition of exogenous activation mixtures [8]. The potential hepatotoxicity of heterocyclic aromatic amines is supported by experimental evidence [9].…”
Section: Introductionmentioning
confidence: 99%